Analisis Pengelolaan Sampah Terkait Pembangunan Polder Kali Banger Di Wilayah Kecamatan Semarang Timur - Suwarno, Anung (Politeknik Negeri Semarang, 2013)
Semarang is a subdistrict of east lowlands adjacent to the shore which consists of 10 villages and a catchment area Banger. Polder is a flood control system and runoff the community based management is a pilot project in Indonesia, located at the eastern most region of Semarang District land surface elevation below sea level tide. Disposal of rain water that fell in the region to the sea or water bodies need to help pump. In connection with the issue of waste management is carried optimal efforts to hold and manage the garbage that is not transported before it goes into the river and impede performance polder pump. One way of method 3R ( Reuse, Reduce and Recycle ) are performed and optimized in research in this area is to chop / grind waste to reduce its volume ( Volume Reducing Waste / VWR ) and to reduce the air content in the waste compaction using tools hydraulic jack with a capacity of 2 ton ( Hidrolic Compactioning System / HCS ). trial was made with two kinds of conditions in the experiment without the waste samples sorted and experiment with sorted. Of waste compaction test by hand without the obtained results are sorted and enumerated volume reduction of 17.3 % (0.000812 m3 from 0.0047 m3 ) determining the value of the correlation coefficient R2 = 0.821 or R = 0.906, it is meaning that compaction can not be optimal because the condition of waste still influenced by the mix of many types of material and content of the air in it. Further trials compaction of waste with hydraulic equipment and waste sorted and chopped / grinded results obtained R2 = 0.885 or R = 0.940, for the meaning that optimal compaction due to the condition of selected waste (organic) and content of the air inside is removed and segregated garbage can be reused or sold. The continued impact of the measures is a reduction in the number of garbage trucks ritation and can save transportation costs and fuel in accordance with national austerity program. In addition, if the waste disposed to landfill (TPA), the volume reduction process will extend the life of the landfill. The new research is a preliminary study to examine the percentage of reduction in production, reduction of production costs and transport costs in managing the waste that does not go in the garbage or dumped into the Banger. The purpose of this paper is one effort to disseminate to the public and local government in the optimal waste management and integrated with the flood disaster management should be in conjunction with waste manage mentand waste water.